Evaluation of the virtual Exercise is Medicine on Campus campaign: effects on college students' physical activity perceptions and behaviors - Avila Martinez, Miriam Catalina (Kansas State University, 2021)
Background/Purpose: The COVID-19 pandemic has negatively affected the mental health and wellbeing of college students, as well as behaviors such as physical activity. Exercise is Medicine On Campus (EIM-OC) calls upon universities and colleges to promote physical activity as a vital sign of health. The aim of this study was to evaluate the reach and effectiveness of the virtual EIM-OC campaign and its effects on college students’ physical activity behaviors and selected social cognitive theory (SCT) variables. As a secondary aim, we also assessed physical activity behavior and barriers among college students during the COVID-19 pandemic. Methods: We conducted an online baseline survey at the end of September 2020 and a follow up survey at the beginning of November 2020. A total of 469 K-State students (n = 362 females; n = 82 kinesiology majors) completed the baseline survey, and 337 of these participants completed the follow-up survey. Throughout October (EIM-OC month), K-State conducted a variety of virtual events to promote physical activity on campus, including Lunch and Learn presentations by Kinesiology faculty, weekly physical activity challenges, a monthlong Bingo challenge, daily social media posts, and a Distinguished Lecture Series presentation. Changes in physical activity and SCT variables (self-efficacy, self-regulation, outcome expectations, and perceived community support) from baseline to follow-up were assessed using parametric and non-parametric tests. Results: Of the 337 individuals who completed the follow up survey, 97 (28.8%) said they had heard of EIM-OC month at K-State. Kinesiology students were significantly more likely to have heard of EIM-OC than non-Kinesiology students ([chi]² = 129.8, p < .001). Paired t-tests revealed there was a small but significant increase in participants’ perceived community support from baseline to follow-up (t = -3.2, p = .002), but no changes in self-efficacy, self-regulation, or outcome expectations. Wilcoxon Signed Rank test results revealed that vigorous activity (Z = -2.78, p = 0.005) and total activity (Z = -3.08, p = 0.002) were significantly lower at follow-up compared to baseline among those who had not heard of EIM-OC, but remained the same among those who had heard of EIM-OC. Overall, roughly half of the sample was classified as high active. Males were more likely to be classified as high active than females at baseline ([chi]² = 12.5, p = 0.002), but not follow-up ([chi]² = 0.304, p = 0.86). COVID-related restrictions, lack of time/being busy, motivation/laziness, and school were common barriers at both time points, and weather was identified as an added barrier at follow-up. Outdoor and campus spaces were most frequently reported as physical activity resources used by participants. Conclusions: Overall, the awareness of EIM-OC was high within, but not outside of, the Kinesiology department. Students reported few changes in physical activity behaviors or targeted SCT variables from baseline to follow-up. Future campaigns should explore diverse strategies for promoting EIM-OC across campus to maximize its reach and effectiveness. Keywords: Exercise is Medicine On Campus; college students; physical activity; physical activity behaviors, self-efficacy, self-regulation, COVID-19, community support
Keywords: Exercise is Medicine On Campus; College students; Physical activity; Self-efficacy; Self-regulation; COVID-19